Neck Flexor and Extensor Muscle Endurance Measurement in Individuals Using Electronic Devices: A Study Protocol - Macwan, Noel Samuel; Tandel, Dixita (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Background: Electronic devices are becoming more and more essential to daily life at work and home. An extended time of neck flexion brought on by using electronic devices more frequently—10 hours a week on average—increases the risk of developing musculoskeletal pain. Repetitive motion and poor posture are common causes of neck strain among laptop users. The motor output of the cervical muscles is impaired in those who have neck pain. Bad postures cause the neck to experience abnormal physiological strain, which weakens the neck's muscles. There is currently insufficient evidence to establish a connection between neck pain, posture, and neck muscular endurance. The study aims to assess neck muscular endurance in healthy persons who use electronic devices in a typical manner. Methodology: In this observational study, normal healthy students from Constituents College of Sumandeep Vidyapeeth will be approached and explained about the study. A toss-of-coin method will be used to select either the student having an odd enrollment number or an even enrollment number from a class to avoid any form of bias. The participants will be screened as per the routine musculoskeletal assessment format. All the participants will be assessed for their neck muscle endurance. Outcome Measures: Neck flexor muscle endurance, Neck extensor muscle endurance. Statistical Analysis: Independent t-test will be done to compare the two groups with neck pain and with no neck pain individuals to know the effect of neck muscle endurance on neck pain. One-way ANOVA will be used to compare more than 3 groups. Conclusion: This observation study will be useful in checking the association of neck muscle endurance on neck pain in individuals using electronic devices. Clinical Trial Registration Number: CTRI/2021/06/034444.